Electronic Contracts and the Personal data Protection of the Consumer: Sources Dialogue Between the Consumer Protection Code and the Internet Civil Mark. - Silva, Rosane Leal Da (2016)
This paper analyzes the personal data protection of the consumer and your vulnerability in interactive electronic contracts, aiming to point means of defense. For this, uses the deductive approach and starts of the electronic contracting to discuss the legal protection of the consumer in light of the capturing and processing of personal data by the furnisher. Considering the absence of law about personal data, concludes that electronic contracting expands the consumer vulnerability, which requires the principles application of the Consumer Protection Code, adding the Internet Civil Mark in relation to the privacy protection.